Answered step by step
Verified Expert Solution
Question
1 Approved Answer
Using Coq, prove by induction that (C B0) (C B1) . . .(C Bn) = C (B0 B1 . . . Bn) Template: Require Import
Using Coq, prove by induction that (C B0) (C B1) . . .(C Bn) = C (B0 B1 . . . Bn)
Template:
Require Import Ensembles.
Variable B : nat -> (Ensemble U). Fixpoint unionB (n : nat) : Ensemble U := match n with | 0 => B 0 | S m => Union U (unionB m) (B (S m)) end. Fixpoint intersectionCB (n : nat) : Ensemble U := match n with | 0 => Setminus U C (B 0) | S m => Intersection U (intersectionCB m) (Setminus U C (B (S m))) end. Theorem generalizedIntersectionSetminusAlt : forall n : nat, intersectionCB n = Setminus U C (unionB n). Proof. induction n. apply Extensionality_Ensembles. (* to be completed *) Qed.
Step by Step Solution
There are 3 Steps involved in it
Step: 1
Get Instant Access to Expert-Tailored Solutions
See step-by-step solutions with expert insights and AI powered tools for academic success
Step: 2
Step: 3
Ace Your Homework with AI
Get the answers you need in no time with our AI-driven, step-by-step assistance
Get Started